Energy forecast of Ecuador’s Tertiary Sector to 2040 Using the LEAP Model - Tigua Villaprado, Yoiler Steeven; Cadena Barrera, Joao Segundo; Castro-Verdezoto, Pedro; Ortega-Pacheco, Daniel (EASI: Engineering and Applied Sciences in Industry, 2025)
This study forecasts energy consumption in Ecuador’s tertiary sector through 2040 using a prospective energy model developed with LEAP software. It relies on official data and variables such as employment figures and household consumption. Three scenarios are analyzed: Business as Usual (BAU), High (HIGH), and Low (LOW) consumption. Results show an 87% increase in energy use between 2020 and 2040, rising from 5 million to 10 million barrels of oil equivalent (BOE). Under the BAU scenario, consumption is projected at 10 million BOE; 6 million in the LOW scenario; and 13 million in the HIGH scenario. Out of 11 activities analyzed, 84% of energy use is concentrated in three key areas: Information and Communication, Commerce, and Accommodation and Food Services. The sector also displays a strong reliance on electricity, which represents 76% of its total energy consumption. Transportation services were excluded from the analysis, as they are considered a separate sector due to their high energy demand. The findings highlight the urgency of implementing sustainable strategies to manage energy use, especially in high-consumption activities. This information provides a valuable foundation for decision-makers and stakeholders in designing energy policies focused on efficiency and reducing environmental impacts in Ecuador’s tertiary sector.